Trends in strong opioid prescription for cancer patients in Japan from 2010 to 2019: an analysis with large medical claims data. (30th July 2022) - Takahashi, Richi; Miyashita, Mitsunori; Murakami, Yoshitaka; OBA, Mari S
Abstract: Background: Consumption of opioids, essential drugs for pain relief, has seen rapid growth worldwide. In Japan, where total opioid consumption still remains low among developed countries, little is known about trends in the clinical patterns of opioids in terminally ill cancer patients. Methods: Patients who died of cancer from 2010 to 2019 were included in this study. Morphine, oxycodone, fentanyl, tapentadol, methadone and hydromorphone were examined as opioids for cancer pain. We calculated the prevalence of prescribed opioids prior to death by year and age group and the average opioid dose 30 days before death. Results: The total number of patients was 221 598. We found that the prescription prevalence of opioids increased from 60.8 to 65.9% (5.1%). Morphine was most prescribed in 2010 but had decreased prevalence (−9.0%) during the 10-year period. Oxycodone had the highest increase in prescription prevalence (13.7%), and fentanyl prevalence decreased (−4.9%). In the subgroup comparison, the prescription prevalence of opioids in the elderly was lower than that in the younger group; however, the increasing trend in the elderly was greater than that in the younger group. The percentage of patients prescribed low-dose opioids (<60 mg/day) during the 30 days before death increased by 4.9% and was the highest throughout the study period. Conclusion: The prevalence of opioid prescriptions for terminally ill cancer patients has increased from 2010 to 2019 in Japan. The opioid-specific trends were similar to the global trend but differed by palliative care specialty. Abstract : The opioid prescriptions for cancer patients has increased in Japan from 2010 to 2019. The opioid-specific trends were similar to the global trend but differed by palliative care specialty.